Penerapan Layanan Bimbingan Klasikal Guna Membangun Kemandirian Belajar Untuk Meraih Prestasi yang Optimal Pada Siswa SMA Negeri 1 Talawi - Syahfitri, Wardana; Hasibuan, Uli Makmun; Zakia, Raudatul; Arista, Nadia (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the effectiveness of classical guidance services in building student learning independence in order to achieve optimal achievement in students of SMA Negeri 1 Talawi. The research method used is the experimental research method, involving students of SMA Negeri 1 Talawi as research subjects. The experimental method is a way to find a causal relationship between two factors that are deliberately raised by researchers by eliminating or setting aside other disturbing factors. The research data was collected through data collection instruments, namely Student Worksheets and Classical Guidance Outcome Assessments to determine the influence or relationship between the variables studied. The results of this study are expected to show that classical guidance services play a very relevant role in improving students’ learning independence, which in turn contributes to improving their academic achievement. The impact of this study is the importance of optimizing the implementation of classical guidance services in schools as a structured effort to equip students with basic independent learning skills to achieve learning success.